P17.15 Barriers and facilitators to uptake of cervical cancer screening among clients attending integrated hiv/sexual and reproductive health clinics in zimbabwe. (13th September 2015) - Sibanda, EL; Ruhode, N; Madanhire, C; Hatzold, K; Cowan, FM
Abstract : Introduction: Cervical cancer is the commonest cancer among Zimbabwean women; HIV positive women are disproportionately affected. Access to cervical cancer screening (CCS) is sub-optimal. To improve access, PSI-Zimbabwe integrated CCS with HIV testing services from September 2013. We used serial qualitative interviews to explore evolution of client views on service integration and barriers and facilitators to CCS uptake. Methods: In-depth interviews were held with clients at four clinics providing integrated services in November/2013–March/2014 and November/2014–March/2015. Interviews were audio-recorded, transcribed, translated and analysed thematically. Results: 32 and 37 women accessing integrated services were interviewed in Phases 1&2 respectively. Participants (aged 18–52 years) included women who had declined CCS and women who had been screened. Demand increased and views on CCS became more positive over time. In both phases women were positive about services being integrated because it enabled i) access to services under one roof; ii) information to spread (many in Phase 1 had not known about CCS before visiting integrated services for other reasons). Other factors that facilitated CCS uptake were i) knowing someone who have suffered/died of cervical cancer, ii) peers iii) having suspicious symptoms iv) free services. Barriers were the same across phases; i) fear of cancer diagnosis which was greater among HIV positive women ii) concern that CCS is complex, women sometimes called it 'an operation' iii) belief that the cervix is very fragile and should not be tampered with, some feared that 'tampering' would cause cancer. Low risk perception was common with many believing that i) only old/HIV positive women are affected, ii) absence of signs/symptoms equates with low risk of disease. Conclusion: Integration has increased access to CCS while also facilitating spread of information on CCS, resulting in more positive views over time. Interventions that address myths/misconceptions are likely to improve uptake of CCS. Disclosure of interest statement: The study was funded by the Integrated Support Programme and no conflicts of interest are declared.